Development of Chemistry Module Based on Science Literacy at MAN 4 Aceh Besar - Rizkia, Noviza; Mujakir; Piska, Irhamna Putri (MANDAILING GLOBAL EDUKASIA, 2024)
The learning process carried out so far at MAN 4 Aceh Besar only uses printed books. Based on interviews obtained from chemistry teachers, it was stated that the printed books available at the school have not been able to improve students' understanding of the material on elemental chemistry. This study aims to produce a valid, practical and effective elemental chemistry learning module. This study uses the R&D (Research and Development) product development research method with the 4D model. The subjects of this study were students of class XII MIA 1 MAN 4 Aceh Besar. The results of the study obtained the validity of the module with a very valid category, the results of the student practicality test were obtained from the practicality questionnaire with a fairly practical category, the results of the effectiveness test were obtained from the results of the student's completeness posttest with a very effective category. Based on the results obtained from the validity, practicality and effectiveness tests, it was concluded that the elemental chemistry module based on scientific literacy at MAN 4 Aceh Besar was included in the valid, practical and effective categories used in the teaching and learning process for elemental chemistry material.